The Different Impacts of g-C3N4 Nanosheets on PVDF and PSF Ultrafiltration Membranes for Remazol Black 5 Dye Rejection - Senol-Arslan, Dilek; Gul, Ayse; Dizge, Nadir; Ocakoglu, Kasim; Uzal, Nigmet (Wiley, 2023)
Membranes combined with nanoparticles are an excellent combination capable of successfully removing various contaminants, such as dyes from wastewater while using very little energy and decreasing pollution. The present study reports an efficient approach for Remazol Black 5 (RB5) dye removal using composite graphitic carbon nitride nanosheets (g-C3N4), polysulfone (PSF), and polyvinylidene fluoride (PVDF) membranes. The membranes were prepared using the phase inversion method, with varying quantities of g-C3N4 nanosheets ranging from 0.1%, 0.2% to 0.3%. The prepared g-C3N4 nanosheets were characterized by FTIR, SEM analyses, and zeta potential measurements. FTIR and SEM studies, contact angle, water permeability, COD, and dye rejection measurements were used to characterize the g-C3N4 nanosheets embedded in PSF and PVDF membranes. After the addition of 0.3 wt% g-C3N4, the water flux of the 0.3 wt% g-C3N4 embedded PSF membrane was the highest, whereas the water flux of the 0.3 wt% g-C3N4 embedded PVDF membrane was the lowest. The ultrafiltration (UF) membrane's performance with g-C3N4 embedded showed an RB5 rejection rate of more than 80% and a COD removal efficiency of more than 45%. The results of the experimental filtration showed that RB5 rejection reached maximum values of 91.3% for 0.1 wt% g-C3N4/PSF, and 85.6% for 0.3 wt% g-C3N4/PVDF.
Gul, Ayse/0000-0002-2305-6408;
Keywords: G-C3N4 Nanosheets; Psf Membrane; PVdf Membrane; Remazol Black 5 Dye Rejection; Ultrafiltration; G-C3N4 Nanosheets